Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 174287774 species occurrences available in GBIF matching the query: { "BasisOfRecord" : [ "is Specimen" ] } The dataset includes 174287774 records from 13582 constituent datasets: 2451 records from Macrobenthos Chukchi Sea, 1986. 101 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 42 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 3 records from A new species and new record of the leafhopper genus Balclutha (Hemiptera: Cicadellidae: Deltocephalinae) from China with key to species. 7 records from Tobrilus methanus sp. n. and Tripyla posolskii sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 1 records from Protozoa ZMK. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 10 records from Review of the cave cricket genus Tamdaotettix Gorochov with a new species and some new descriptions (Orthoptera: Rhaphidophoridae, Aemodogryllinae). 2 records from A new limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from Khao Sam Roi Yot massif, peninsular Thailand. 74 records from Reptiles de la expedición al Río Apaporis - Proyecto Colombia BIO. 81 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 55 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 425 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 8 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 48 records from Tardigrad collection of the National Museum of Nature and Science. 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 3 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 14 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 20627 records from Herbier Louis-Marie (QFA) - Collection de lichens. 122 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 241 records from Amphibian Specimens of the Yamagata Prefectural Museum. 28 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 5 records from A new sponge species of the genus Antho (Demospongiae, Microcionidae) from the Tyrrhenian deep Sea. 607514 records from Plant. 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 3 records from Dactylogyrids (Monogenea) parasitic on marine fish from Peru including the description of a new species of Haliotrema Johnston & Tiegs, 1922 and two new species of Parancylodiscoides Caballero & C. & Bravo-Hollis, 1961. 169 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 7 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 21 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 122 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 561 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 9 records from Four new species of Diptilomiopinae from China (Acari: Eriophyoidea: Diptilomiopidae). 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 6 records from New ants (Hymenoptera: Formicidae) from Micronesia. 3 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 4 records from A new anchialine species of Naushonia (Decapoda: Gebiidea: Laomediidae) from the Bahamas. 12859 records from Colecção Entomológica IIA. 1306 records from Flora genérica de las gramíneas del estado de Tlaxcala. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1 records from Zur Kenntnis der Lithobiiden. 3 records from A new genus of Hemerobiidae (Neuroptera) from Baltic amber, with a critical review of the Cenozoic Megalomus - like taxa and remarks on the wing venation variability of the family. 2 records from A new species of Paraleptophlebia Lestage, 1917 (Ephemeroptera: Leptophlebiidae) and a re-description of adults for Paraleptophlebia westoni Imanishi, 1937 with the first description of the larva, from the Russian Far East. 2 records from Phasmarhabditis bonaquaense n. sp. (Nematoda: Rhabditidae), a new slug-parasitic nematode from the Czech Republic. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 3 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 22166 records from Natural History Museum Maastricht (NL) - Herbarium. 7148 records from DMNS Egg Collection (Arctos). 9404 records from MZL Invertebrate Collections. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 1303 records from Crustacean specimens of Bihoro Museum. 1095 records from A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae - Grewioideae). 17 records from New genus and species of cockroaches from the tribe Brachycolini (Blattaria Blaberidae: Blaberinae) and redescription of the Hormetica strumosa. 14923 records from Lepidopterous specimens of Yamagata Prefectural Museum. 7081 records from Invertebrates of the river Tana Basin in Kenya available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section. 17114 records from Collection of Coleoptera. 64 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 221 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 20 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 1 records from Orthoptera - SMF. 1 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 71 records from Revision of New World Cosmorrhyncha Meyrick, 1913 (Lepidoptera: Tortricidae: Olethreutinae), with descriptions of five new species. 2 records from Unveiling the morphology of the Oriental rare monotypic ant genus Opamyrma YAMANE, BUI & EGUCHI, 2008 (Hymenoptera: Formicidae: Leptanillinae) and its evolutionary implications, with first descriptions of the male, larva, tentorium, and sting apparatus. 1372 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 1 records from Wrong side of the leaf: assigning some Lithocolletinae species (Lepidoptera: Gracillariidae) to their proper genera. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 13 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 1702 records from BioGIS - Bryophytes - HUJ collections. 752 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 9 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 1 records from A new species of Silba (Diptera; Lonchaeidae) associated with figs. 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 818963 records from Queensland Museum provider for OZCAM. 10 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 10 records from A taxonomic reappraisal of the Smooth Slug Snake Asthenodipsas laevis (Boie, 1827) (Squamata: Pareidae) in Borneo with the description of two new species. 54910 records from Herbarium Universitatis Daugavpiliensis. 6 records from Taxonomy of the European Pied Flycatcher Ficedula hypoleuca (Aves: Muscicapidae). 672 records from Colección de Entomología - Curculionidae. 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 10 records from On the genera Ptiloneura Enderlein, Loneura Navás, and Loneuroides García Aldrete (Psocodea: ‘ Psocoptera’: Ptiloneuridae). 1 records from Neotropical Monogenoidea. 60. Two new species of Gyrodactylus (Monogenoidea: Gyrodactylidae) from the armored-catfish, Pareiorhaphis parmula Pereira (Loricariidae) and from the cascarudo, Callichthys callichthys (Linnaeus) (Callichthyidae) from Brazil. 251 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 30 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 6 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 3 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 16542 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 3 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 6237 records from Plecoptera. 52 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 9 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 10 records from Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini. 16 records from A review of New World Malaxa (Hemiptera: Fulgoroidea: Delphacidae). 14 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 3 records from Benthic hydroids (Cnidaria: Hydrozoa) from off George V Coast (East Antarctica). 280 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 5 records from Redescription and phylogenetic analysis of the type species of the giant pill-millipede genus Sphaeropoeus Brandt, 1833 (Diplopoda, Sphaerotheriida, Zephroniidae). 24 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 34 records from NZCS Brownsberg Nature Park Monitoring. 141 records from Review of the genus Paramesius Westwood, 1832 (Hymenoptera: Diapriidae, Spilomicrini) from Russia, with description of four new species. 44802 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 59 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 17 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 2 records from New Zealand forest-dwelling skinks of the Oligosoma oliveri (McCann) species-complex (Reptilia: Scincidae): reinstatement of O. pachysomaticum (Robb) and an assessment of historical distribution ranges. 6 records from COI mtDNA barcoding and morphology for species delimitation in the spider genus Ixchela Huber (Araneae: Pholcidae), with the description of two new species from Mexico. 101 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 25 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 2311 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 15 records from Additions to the ichthyofauna of the Tristan da Cunha Group, South Atlantic Ocean.. 3251 records from Inventario florístico de la Sierra de Huautla, Morelos. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 15 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 26 records from Carpoteca de Frutilla del Banco de Germoplasma de Frutilla - Universidad Nacional de Tucumán, Argentina. 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 7 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 4 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 16 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 29842 records from University of California Santa Barbara Invertebrate Zoology Collection. 8 records from Revision of the genus Systellapha Enderlein (Micropezidae, Taeniapterinae). 10 records from Ten new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Southeast Asia. 2 records from Neue Milbenarten aus Kärnten. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 177 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 66639 records from Entomology Collection at the Natural History Museum of Utah. 3 records from Three new species of the genus Xizicus (Orthoptera: Tettigoniidae: Meconematinae) from Taiwan. 4 records from Four new Megaselia species (Diptera: Phoridae) from animal carcasses in Bangi, Malaysia. 6390 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 11 records from Visual Plants (144.41.33.158) - Herbarium specimens from "LOJA" Ecuador. 6 records from A PArtial Skeleton of the Tyrannosaurid Dinosaur Aublysodon from the Upper Cretaceous of New Mexico. 1 records from An interesting new genus of Berothinae (Neuroptera: Berothidae) from the early Eocene Green River Formation, Colorado. 365 records from Colección Herpetológica de la Patagonia. 4 records from On Plesionika persica (Kemp, 1925) and P. reflexa Chace, 1985 (Crustacea: Decapoda: Pandalidae) from India. 1 records from Description of a new species of genus Trachischium with a redescription of Trachischium fuscum (Serpentes: Colubridae: Natricinae). 4 records from Ceraeocercus Uvarov, a genus recorded in China for the first time (Orthoptera, Tettigoniidae; Tettigoniinae; Drymadusini). 119480 records from ALCB - Herbário Alexandre Leal Costa. 3184 records from Herbarium specimens of Limoges university (LIMO). 4847 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 1 records from Earthworm species in various land use systems in the Campos Gerais region of Lapa, Paraná, Brazil. 128557 records from Fish specimens of Kagoshima University Museum. 13649 records from UTEP Invertebrates (Arctos). 4185 records from Diptera Collection of Museum and Institute of Zoology PAS. 233 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 2 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 23 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 770 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 41 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 1567 records from Flora útil del Municipio de la Huerta, Jalisco. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 1353 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 30 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 18 records from Six new species of the genus Nazeris (Coleoptera, Staphylinidae, Paederinae) from China. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 9 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 294 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 23 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 116719 records from Naturalis Biodiversity Center (NL) - Crustacea. 25 records from Brown algae specimens of Komatsu City Museum. 12147 records from Danish Ants (Formicidae). 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 70 records from The genus Hoplothrips in Australia (Thysanoptera, Phlaeothripinae), with eleven new species. 25098 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 207 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 2404 records from The Broward College Insect Collection. 370 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 1 records from Redescription of Leptogyra bujnitzkii (Gorbunov, 1946) comb. nov., the first representative of the gastropod subclass Neomphaliones from the high Arctic. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 24283 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 11 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 30 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 59626 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 2 records from On the identity of the genus Flavoperla (Plecoptera: Perlidae), with description of a new species in southwestern China. 17 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 2 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 5 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 4189 records from Weber State University Herbarium. 5 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 2 records from A new slipper lobster of the genus Petrarctus Holthuis, 2002 (Crustacea, Decapoda, Scyllaridae) from Southwest coast of India. 4 records from New species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Brazil and Suriname. 2 records from A new record of the family Isonychiidae (Insecta: Ephemeroptera) from the Western Ghats, India with a description of new species. 18 records from A new genus for the freshwater crab Potamonemus asylos Cumberlidgeı 1993 ı (Brachyura: Potamoidea: Potamonautidae) from Cameroonı Central Africaı with a key to the genera of the Potamonautinae. 7 records from One new species and one newly recorded species of Cyllodes Erichson from China (Coleoptera: Nitidulidae: Nitidulinae). 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 1 records from A new name for Dendronephthya kukenthali Gravier, 1908 (Octocorallia, Nephtheidae): Dendronephthya perezi nom. n.. 39 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 19021 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planctónicas más frecuentes en el Golfo de California. 2 records from A new species of Hypsohapsis (Heteroptera: Schizopteridae: Hypselosomatinae) from the Brazilian Amazon. 22 records from A revision of the genus Disparalona (Cladocera, Chydorinae) in South America. 2140 records from Captive Primate Specimens of Japan Monkey Centre. 11 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 52873 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 36 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 18 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 1971 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 12 records from A Catalogue and Historical Study of the Odonata of Ecuador. 4621 records from Códigos de barras de la vida en peces y zooplancton de México. 49 records from The genus Litophyton Forskål, 1775 (Octocorallia: Alcyonacea: Nephtheidae) from Australia. 3 records from A new fossil species of Pycnomerus Erichson (Coleoptera: Zopheridae) from Baltic amber, and a replacement name for a Recent North American congener. 62324 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 1 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 27 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 27 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 342 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 25 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 3035 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 5 records from Loricifera - SMF. 878 records from COA Bird Collection (Arctos). 9 records from New records and their associated DNA barcodes of the butterfly family Hesperiidae in Tibet, China. 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 4 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 10654 records from Bryophyte specimens of The Nagoya University Museum. 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 34520 records from University of Guam Insect Collection. 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 22857 records from National Botanic Garden Belgium - Myxomycetes. 47 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 5 records from Review of the fossil record of Bolitophilidae, with description of new taxa and discussion of position of Mangas Kovalev (Diptera: Sciaroidea). 3 records from Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru. 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 196 records from Collection des mammifères d'Auvergne. 9 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 8 records from Report on a collection of dragonflies (Odonata) from the Andaman Islands.. 12 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 25 records from Morphologische Daten von Natrix. 7 records from Taxonomic revision of the epigean representatives of the spider subfamily Harpacteinae (Araneae: Dysderidae) on the island of Crete. 3 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 2 records from First record of Orthelimaea himalayana (Ingrisch, 1990) (Orthoptera: Tettigoniidae: Phaneropterinae: Elimaeini) from India with description of its female. 3072 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche. 4 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 2 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 5 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 54 records from Revision of the Garra species of the Hajar Mountains in Oman and the United Arab Emirates with the description of two new species (Teleostei: Cyprinidae). 118 records from Collection botanique Lamy de la Chapelle E. (BOUM). 12644 records from Brown University Herbarium. 1189 records from UWIZM Molluscs. 277 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 9 records from Key to the currently recognized species of Limnias Schrank, 1803 (Rotifera, Monogononta, Gnesiotrocha, Flosculariidae). 5514 records from MCP-Aves - Coleção de Aves. 2 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 98 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 7 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 9 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 6065 records from LISU Herbario Angola. 4687 records from nhmc_ob_2019. 824 records from Bird specimens of Saitama Museum of Natural History. 382 records from orthopteracollections-nhmj-ioj. 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 9 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 626 records from Mycology collection, Norwegian Forest and Landscape Institute. 24370 records from Muséum d'Avignon. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 7582 records from Tropical epiphyte diversity under human impact ? Comparing primary forests, secondary forests, and forest fragments in Ecuador - Otonga. 20 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 4 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 5 records from Description of two new species of the genus Automate De Man, 1888 (Crustacea: Decapoda: Caridea) from the South China Sea. 7 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 218 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 148 records from BioAcoustica: Wildlife Sounds Database. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 42 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 55 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 7 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 1 records from Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand. 8 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 197 records from TransForest - vegetation, lichen and fungi data 2016. 3 records from Otacilia fansipan spec. nov., the second congener recorded from Vietnam (Arachnida: Araneae: Phrurolithidae). 173 records from UWIZM Anoles. 3 records from New species of Alpinalona Alonso & Sinev, 2017 (Cladocera: Anomopoda: Chydoridae) from South-East USA. 10 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 252 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 1 records from Nothrus pulverulentus. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from The Indian net-casting spider name Deinopis goalparaensis Tikader & Malhotra is a nomen dubium (Araneae: Deinopidae). 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 1268 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 155 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 12 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 149 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 1158 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 83 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 22 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 4 records from Haematophagous biting midges of the extant genus Culicoides Latreille (Diptera: Ceratopogonidae) evolved during the mid-Cretaceous. 1957 records from SIM-Fungal records compiled by Joan Montón. 6 records from Nueva especie de Aleuropleurocelus Drews y Sampson (Hemiptera: Aleyrodidae) y clave para especies del grupo de forma oval. 783924 records from Western Australian Museum provider for OZCAM. 6 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 3998 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 424 records from Mamíferos voladores y no voladores del suroccidente colombiano. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae). 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 37 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 53215 records from Naturalis Biodiversity Center (NL) - Diptera. 2 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 1 records from Berlese's Primitive Oribatid Mites. 18 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 203 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 12 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 307 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 6 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 110 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 97 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 16 records from Insect Collections of Okomu National Park- Nigeria. 52383 records from University of Minnesota Insect Collection. 139635 records from ARABEL - Arachnologia Belgica. 95 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 9 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 4792 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 34 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 8 records from A new species of Paralithoxus (Siluriformes: Loricariidae: Ancistrini) from the highlands of Serra da Mocidade, Roraima State, Brazilian Amazon. 15 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 697 records from 2019_NSMK_PL. 71 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 39 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 1872 records from Herbier National de Guinée (HNG). 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 14 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 300 records from EDIT - ATBI in Gemer area (Slovakia). 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 182 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 7 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 4926 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 5 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 20941 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 39 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 159 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 4546 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 1 records from 3. Descriptions of new Genera and Species of Odonata in the Collection of the British Museum, chiefly from Africa.. 33 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 6 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 6 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 15614 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 310 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 6 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 616 records from ENBI WP 13 Martius C. F. P. von Collection subset (Muenchen). 2568 records from Fish (NHMK-PI). 7 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 174 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 34 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 844 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 2 records from Phylogeny of Bathysciotina Guéorguiev, 1974, based on morphology with a special emphasis to Italian genera and with the description of a new species of Halbherria (Coleoptera Leiodidae Cholevinae Leptodirini). 2 records from A New Genus And Species Of Panaphantina (Coleoptera: Staphylinidae: Pselaphinae: Euplectitae: Trichonychini) From Australia. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 19 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 2 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 6 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 345 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 1 records from Acantorna-a new genus of Hymedesmiidae (Porifera, Demospongiae Poecilosclerida) from the western Aleutian Islands of Alaska with description of Acantorna tahoma n. sp.. 2 records from A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India. 19 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 9489 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 5 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 7887 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 750 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 6 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 15 records from Conringia orientalis. 5 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 3 records from A new subfamily, Styracurinae, and new genus, Styracura, for Himantura schmardae (Werner, 1904) and Himantura pacifica (Beebe & Tee-Van, 1941) (Chondrichthyes: Myliobatiformes). 50 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 1298 records from Vermont Orthoptera Records from Historic Dot Maps. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 3933 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 11 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 11 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 7873 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 19 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 381 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 29 records from Herbarium Senckenbergianum (FR) - Protista. 250 records from Colección de helechos de la FML. 3 records from Zoology in the Middle East. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 24 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 159 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 4447 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 189 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 29 records from Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region. 1 records from New record of the genus Baetiella Uéno, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 1 records from The tadpoles of Murree Hills Frog Nanorana vicina (Anura: Dicroglossidae). 622 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 6 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 204469 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 10 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 6 records from Two new species of Guyruita Guadanucci et al., 2007 (Araneae, Theraphosidae) from Brazil. 24 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 2 records from A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific. 134 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil. 3 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 21884 records from Birds Specimens. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 6 records from Contributions to the study of Idiocerinae (Homoptera: Auchenorrhyncha: Cicadellidae) of Central Asia with notes on synonymy. 208 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 1952 records from ISM Ichthyology Collection. 92 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 20220 records from DMNS Mammal Collection (Arctos). 1 records from A new species of the genus Pachytriton (Caudata: Salamandridae) from Hunan and Guangxi, southeastern China. 5 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 6 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 82 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 785 records from Colección de Mamíferos Marinos del Centro Nacional Patagónico. 264 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 5 records from Cryptic species among bumblebee mimics: an unrecognized Hemaris hawkmoth (Lepidoptera: Sphingidae) in eastern North America. 108701 records from The Himalayan Uplands Plant database (HUP Version 1). 15 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 11 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 5 records from New data on jumping spiders of Iran, with a new species of Salticus (Araneae: Salticidae). 29340 records from National Museum of Natural Science. 8425 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 458 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 14 records from First record of the genus Dictyopharina Melichar, 1903 (Hemiptera: Fulgoroidea: Dictyopharidae) from China, with descriptions of two new species. 23 records from Taxonomic Accounts With Notes On Spatial Diversity And Relative Abundance Pattern Of Horseflies (Diptera: Tabanidae) From Sonamukhi Protected Forest Area Of West Bengal, India. 104 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 1 records from A new species of Ascidiacea (Herdmania andamanensis sp. nov.) from Andaman and Nicobar Islands, India. 254 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 17 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 142 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 6336 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 322 records from Collections ichtyologiques et herpétologiques (BOUM). 1584 records from MCP-Mamiferos - Coleção de Mamíferos. 4 records from Description of Rhamma dawkinsi (Lepidoptera: Lycaenidae) a new mountain butterfly from Colombia. 236 records from The Echinoderm Fauna of the Azores (NE Atlantic Ocean). 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 13 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 73 records from Revision Of The Spider Genus Neoanagraphis (Araneae, Liocranidae). 1 records from Norwegian Lepidoptera working group. 26 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 7 records from New biogeographical makeup for colonisation of the Baja California Peninsulaı with the description of a new Onthophagus (Coleoptera: Scarabaeidae: Scarabaeinae). 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 38876 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 14 records from Three new species and three new records of the genus Bamboosiella from China (Thysanoptera: Phlaeothripidae). 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 3 records from Description of a new species of the genus Agamura Blanford, 1874 (Squamata: Gekkonidae) from southern Iran. 2 records from A new Panolis Hübner, [1821] species from Vietnam (Lepidoptera, Noctuidae, Orthosiini). 1 records from Archaeomalthus - (Coleoptera, Archostemata) a ‘ ghost adult ’ of Micromalthidae from Upper Permian deposits of Siberia?. 3 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 3 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 973 records from Zambian Bat Collections Worldwide. 466 records from PSU-Seagrass Collection. 8 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 28 records from A new freshwater shrimp species of the genus Palaemon Weber, 1795 (Decapoda: Caridea: Palaemonidae) from northeastern Japan. 270 records from bmhs_weatherheadshell_collection. 598 records from Entomological collection of the National Museum. 234 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 277 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 1 records from Miriapodi di alcune grotte della Campania. 5 records from A new species of the greeneye genus Chlorophthalmus (Teleostei: Chlorophthalmidae) from the central North Pacific. 4 records from Campydoroides manautei gen. et sp. nov. from New Caledonia and a reappraisal of the suborder Campydorina (Nematoda). 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 22 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 285727 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 8 records from More cautionary tales: family, generic and species synonymies of recently published taxa of ghost and mud shrimps (Decapoda: Axiidea and Gebiidea). 7 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 220 records from Living Cirripedia. 11 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 9 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 151 records from Helmintos parásitos de peces del sureste de México. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 2 records from Cnemaspis rajakarunai sp. nov., a rock dwelling day-gecko (Sauria: Gekkonidae: Cnemaspis) from Salgala, an unprotected lowland rainforest in Sri Lanka. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 11 records from A new species of Neobathyclupea from the northern Indian Ocean with comments on N. malayana (Teleostei, Perciformes, Bathyclupeidae). 2 records from A new pseudoscorpion genus from western Georgia (Pseudoscorpiones: Neobisiidae: Cornuroncus n. gen.), with a key to all Neobisiinae genera. 39 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 677 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 150 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 5615 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 204 records from Echinoderms from the Seaflower Biosphere Reserve. 25 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 291495 records from Allan Herbarium (CHR). 1 records from Pinguisoperla, a new fossil genus of Perlidae (Insecta: Plecoptera) from mid-Cretaceous Burmese amber. 256522 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 4 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 69 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 14275 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 27 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 1480 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 8 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 5 records from Cladocera from the Upper Xingu River Basin with the description of a new genus of the Chydoridae (Crustacea: Branchiopoda: Anomopoda). 4 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 13 records from Coleção de Coleoptera da Universidade de Brasília. 5428 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 31 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 28108 records from Marie-Victorin Herbarium (MT) - Bryophytes. 62 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 330 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 3 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 9 records from The genus Jeekelosoma Mauriès, 1985 - Moroccan cave millipedes (Diplopoda, Polydesmida, Paradoxosomatidae). 83 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 10 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 3158 records from Utah State University, Intermountain Herbarium. 4 records from The identity of Osteobrama cotio, and the status of “ Osteobrama serrata ” (Teleostei: Cyprinidae: Cyprininae). 866 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 978 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 251625 records from CAS Entomology (ENT). 39742 records from Naturalis Biodiversity Center (NL) - Pisces. 32 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 25 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 320 records from Myxomycetes collection of the University of Eastern Finland. 47 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 20 records from New data on the fauna of China, part I: the taxonomy of the millipede family Julidae (Diplopoda). 7 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 17713 records from NCSM Mammals Collection. 100 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 96290 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 57 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 14 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 1 records from On the Chilopoda from Turkey. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 9 records from A contribution to taxonomy of the superfamily Grylloidea Laicharting from Yunnan, China (Orthoptera: Grylloidea). 7 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 4207 records from CASES2003_2004. 376 records from Digitalización y sistematización de las colecciones biológicas del INECOL. 3 records from Nouvelles fourmis de Madagascar.. 152 records from CHAS Botany Collection (Arctos). 20 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 9 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 47 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 13 records from Visual Plants (144.41.33.158) - Private collection of Florian Werner. 836 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 70 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 27 records from Review of Neocynorta Roewerı 1915 with two new generic synonymies (Opiliones: Gonyleptoidea: Cosmetidae). 7814 records from Odonata de Veracruz. 621 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 712 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 3 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 15 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 3 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 5042 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 11 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 127 records from Collection Ephemeroptera - SMF. 242 records from FBIP: Identification of polychaetes used as bait. 102476 records from Denver Museum of Nature & Science - Entomology. 12 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 34829 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 35 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 74 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 9000 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 221 records from Revision of the genus Dziriblatta Chopard, 1936 (Blattodea, Ectobiidae, Ectobiinae) from North Africa, Spain, and the Macaronesian islands. I. The nine subgenera of the genus. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 8 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 10212 records from Spider (NSMK-SP). 30608 records from OUPR - Herbário "Professor José Badini". 64 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 433 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 101 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 1 records from First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species. 10650 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 42 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 1 records from Resurrection of the earthworm species Dendrobaena fedtschenkoi (Michaelsen, 1900), a former synonym of Dendrobaena byblica (Rosa, 1893) (Clitellata: Megadrili). 5 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 6 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 2 records from A new species of Yllenus Simon, 1868 from northern India (Araneae, Salticidae). 77 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 1 records from A new species of Ohilimia Strand, 1911 from New Guinea (Araneae: Salticidae). 2 records from The fossil crown wasp Electrostephanus petiolatus Brues in Baltic Amber (Hymenoptera, Stephanidae): designation of a neotype, revised classification, and a key to amber Stephanidae. 477 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 8 records from Données taxonomiques et éthologiques nouvelles sur quatre espèces de Cigales du Sud thaïlandais (Rhynchota, Cicadoidea, Cicadidae). 12 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 3 records from A new species of the genus Sovia Evans, 1949 from South Central Yunnan, China (Lepidoptera, Hesperiidae). 11 records from The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea. 2007 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 9 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 4221 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 9 records from The bark louse family Stenopsocidae (Psocodea: Psocomorpha) newly recorded from Laos, with description of three new species. 5 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 2 records from Holorchis castex n. sp. (Digenea: Lepocreadiidae) from the painted sweet-lips Diagramma pictum (Thunberg, 1792) (Perciformes: Haemulidae) from New Caledonia. 604 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 146 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 37 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 36 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 5710 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 2 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 293 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 43770 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 1 records from A new species of the genus Megophrys (Anura: Megophryidae) from Yunnan Province, China. 174 records from Antarctic pycnogonids. 62799 records from MLZ Bird Collection (Arctos). 14 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 26 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 3 records from Redescription of Honduriella maxima Denmark & Evans (Acari: Mesostigmata: Phytoseiidae), description of a new species of Honduriella Denmark & Evans from the Amazonian Forest, and a modified characterisation of the genus. 39 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 15 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 4976 records from Gastropod Specimens of the Yamagata Prefectural Museum. 6 records from Two new species of Nemouridae (Plecoptera) from Vietnam. 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 385 records from UWYMV Herpetology Collection (Arctos). 107332 records from Herbarium Senckenbergianum (FR) - Fungi. 2000 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 8 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 2257 records from Plant specimens of Bihoro Museum. 232 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 25 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 944 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 6 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 79 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 22 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 394 records from Reptilia ZMK. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 3 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10898 records from Inventario de Hymenóptera; parasítica en México. 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 3004 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 124 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 3712 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 817 records from Lucanidae. 267243 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 6 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘ Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 5 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 408 records from Birds Specimens of Akita Prefectural Museum. 2 records from Delimiting the snapping shrimp Alpheus lobidens De Haan, 1849 (Caridea: Alpheidae) based on morphological and molecular data. 3 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 2 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 3 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 5 records from Certain species of Plecoptera from the headwater springs of National Integration River (São Francisco), Brazil. 26841 records from MSUM Ichthyology and Herpetology Collections. 25 records from Two new species of the gobiid fish Trimma from the coral reefs of the western Pacific Ocean (Pisces; Perciformes; Gobioidei).. 407 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 8 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 7 records from A new species of Dwarf Japalura sensu lato (Reptilia: Squamata: Agamidae) from the upper Mekong River in Eastern Tibet, China, with notes on morphological variation, distribution, and conservation of two congeners along the same river. 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 62210 records from Tiroler Landesmuseum Ferdinandeum. 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 89 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 23 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 68 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 78 records from Mammals (GNHM-MM). 2 records from The first Cacomorphocerus species (Coleoptera, Cantharidae) from Rovno amber a second species of the genus with 11 - segmented antennae. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 12 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 3 records from F. L. de Castelnau’s Norman River fishes housed in the Macleay Museum, University of Sydney. 1 records from One new species of Amphinemura and description of the female of A. ancistroidea Li & Yang (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China. 3 records from Species status of Colias misti (Pieridae: Coliadinae) from the Arequipa region South Peru, and a description of its new subspecies, from Cotahuasi canyon South-Central Peru. 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 351 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 8 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 660 records from Collection Hydrozoa - ZSM München. 2 records from Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality. 202480 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 10 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 2 records from A new species of Tyrannoseira (Collembola: Entomobryidae: Seirini) from the Brazilian coastal region. 34 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 36162 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 6 records from Pristipomoides amoenus (Snyder 1911), a valid species of jobfish (Pisces, Lutjanidae), with comparisons to P. argyrogrammicus (Valenciennes 1832). 22 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 5 records from A new species of snook, Centropomus (Teleostei: Centropomidae), from northern South America, with notes on the geographic distribution of other species of the genus. 36 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 18 records from Tyrannosaurus And Torosaurus, Maestrichtian Dinosaurs From Trans-Pecos, Texas. 6 records from Description of a new species of deep-water snake eel, Ophichthus mccoskeri (Ophichthidae: Ophichthinae) from Andaman Sea, India. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 5 records from A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus. 77 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 440 records from Wichita State University Collection. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 14 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 647 records from pbzt_insect_biodiversity. 7 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 281 records from NZCS Upper Tapanahony Expedition 1991. 1 records from Oppia nitens. 7 records from Three new species and one new record of Torrenticolidae (Acari, Hydrachnidia) from Wuyishan with an updated key for Chinese fauna. 24 records from Tanzanian Vertebrate Collection. 42 records from Ovomanonychus, a new genus of South American Sericoidini (Coleoptera Scarabaeidae: Melolonthinae). 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 2 records from First Jurassic grasshopper (Insecta, Caelifera) from China. 57928 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 54 records from Anfibios y reptiles de la serranía las Quinchas, Boyacá - Proyecto Boyacá BIO. 7 records from Philippogalla, a new genus for Philipposcopus modestus (Baker) from the Philippines, and a new species of Philipposcopus (Hemiptera: Cicadellidae: Idiocerinae) from China. 10 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 6 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 128 records from Coleção de Nematoda do Museu Nacional - UFRJ. 8 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 3 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 9 records from One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China. 22 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 4728 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 7 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 2740 records from Fungi specimens of Saitama Museum of Natural History. 1129 records from Mollusca Collection of Saitama Museum of Natural History. 31 records from Three new species of Diduga Moore, [1887] (Lepidoptera, Erebidae, Arctiinae) from Cambodia. 5 records from Thalassironus filiformis sp. nov. (Nematoda, Enoplida) from the South China Sea. 7 records from Three new species of Epigomphus (Odonata: Gomphidae) from Costa Rica. 2 records from New ichneumonids (Hymenoptera, Ichneumonidae) from the Eocene Tadushi Formation, Russian Far East. 12 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 6 records from Two new species of the spider genus Wanniyala Huber & Benjamin, 2005 (Araneae Pholcidae) from Sri Lanka. 91 records from Phytoseiid mites (Acari: Phytoseiidae) associated with tropical ornamental plants, with a checklist and a key to the species of Bahia, Brazil. 374 records from Medicinal potential of African plants (Togo). 8330 records from Nijmegen Natural History Museum (NL) - Herbarium. 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 10738 records from The Suguru Igarashi Insect Collection (Lepidoptera: Lycaenidae) of The University Museum, The University of Tokyo. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 82 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 8 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 13590 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 17 records from Review of the genus Paradonus Stibick, 1971 (Elateridae: Negastriinae), with three new North American species. 4 records from Description of a new species of Andaeschna (Odonata: Aeshnidae) from the Western Colombian Andes. 94493 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 139 records from A new western Canadian record of Epeoloides pilosulus (Cresson). 4837 records from Free-living marine Nematodes from San Antonio and Cormoranes sandy beaches (Rio Negro, Argentina), 2006.. 1313 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 6 records from A revision of Holothuria (Halodeima) kefersteinii (Selenka, 1867) and the revival of Holothuria inornata Semper, 1868 from sea cucumbers collected in Mexico and Central America. 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 26718 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv). 39 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 8 records from New species of grasshopper genus Aptoceras Bruner, 1908 (Orthoptera, Acrididae, Ommatolampidinae, Ommtolampidiini) from Iguaçu National Park (Southern Brazil), including a taxonomic key and distribution data. 227 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 2 records from Contributions to the palaeofauna of Ptinidae (Coleptera) known from Baltic amber. 173415 records from Hymenoptera specimen database of Kyushu University. 3428 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 16 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 2097 records from Finnish Floristic Database (Literature Sources). 174 records from The Myriapoda Collection of the National Museum of Nature and Science. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 27 records from Review of the genus Elasmostethus (Hemiptera: Heteroptera: Acanthosomatidae) from the Korean Peninsula. 11472 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 7 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 2 records from A new species of anole from Parque Nacional Volcán Arenal, Costa Rica (Reptilia, Squamata, Dactyloidae: Norops). 8406 records from Conservatoire Botanique Pierre Fabre. 7 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 100 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 3 records from А new species of Alona Baird, 1843 (Cladocera: Chydoridae) from the ancient Lake Ohrid. 1309 records from Mongolian Plant (MMNH-PL). 23 records from Synopsis of world Discleroderma Kieffer (Hymenoptera, Bethylidae). 2 records from Description of Penia mantillerii sp. nov. (Coleoptera: Elateridae: Dimini), with a key to Penia species from Vietnam and nearby areas. 29 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 14 records from Cladistic analysis and synopsis of Chloropepla Stål (Hemiptera: Heteroptera: Pentatomidae) with the description of three new species. 46 records from A check list of the Chinese Zeugophorinae (Coleoptera: Megalopodidae), with new synonym, new record and two new species of subgenus Pedrillia from China. 80 records from An updated checklist of Iranian Encyrtidae (Hymenoptera, Chalcidoidea). 71 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 33 records from Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae). 4 records from Molecular phylogeny of Hiptage (Malpighiaceae) reveals a new species from Southwest China. 4 records from A new species of Lamprodila (Ovalisia Kerremans, 1900) (Coleoptera: Buprestidae) from Sulawesi, Indonesia. 8 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 35 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 1095 records from Amphibian specimens of Kanagawa Prefectural Museum of Natural History. 22 records from A new species of the genus Verilus (Teleostei, Percomorpha, Acropomatidae) from Brazil. 18 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 1594 records from Musée Vert ornithology collection. 896 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 20 records from Nine new Trechisibus species from Peru and Argentina (Coleoptera: Carabidae: Trechinae). 36 records from Review of Chinese species of the Oxylipeurus - complex (Phthiraptera: Philopteridae), with descriptions of two new genera and five new species. 35897 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 61798 records from Fiocruz/CMN - Coleção de Mosquitos Neotropicais. 2 records from Porifera ZMK. 1 records from Nothrus furcatus. 41 records from Description of two new species of Regalana and a new genus of Gyponini (Hemiptera: Cicadellidade: Iassinae). 9 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) VIII. The densimacularis species group, with descriptions of four new species. 4 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 17 records from A new species of Victrix Staudinger, 1879 from Kazakhstan (Lepidoptera, Noctuidae). 12 records from Redescription and lectotype designation of Chasmogenus abnormalis (Sharp), with notes on its distribution. 56 records from Revision of the genus Tmesiphorus LeConte, 1849 (Coleoptera: Staphylinidae: Pselaphinae) from Japan. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 1 records from Oribates flammula. 97351 records from University of Tennessee Bryophyte Herbarium. 11001 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 265 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 2 records from Bioacoustics review of Anatolian species of the predatory bush-cricket genus Saga (Orthoptera: Tettigoniidae: Saginae) with the description of a new species. 30433 records from Fish (NSMK-PI). 11 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 70 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 17 records from The Afrotropical braconine genus Dioxybracon Granger with descriptions of four new species and new generic synonymy. 25 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 19 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 14009 records from Collection Trichoptera - SMF. 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 235 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 126 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 108313 records from Arizona State University Hasbrouck Insect Collection. 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 429 records from Collection Strepsiptera SMF. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 3381 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 57 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 5316 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 3383 records from Lista florística de la Costa Grande del estado de Guerrero. 12 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 346 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 165 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 10 records from A New Genus And Species Of Orsillinae (Heteroptera: Lygaeoidea: Lygaeidae) From Argentina. 2 records from Two new pill millipedes (Diplopoda: Glomerida: Glomeridae) from high mountains of Vietnam. 46057 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 83 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 18 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 5 records from Four new Oriental species of the ‘ Cephennomicrus group’ (Coleoptera: Staphylinidae: Scydmaeninae). 79 records from Catalogue of the Syrphidae of Egypt (Diptera). 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 2126 records from Dolichopodidae of Portugal - dataset 2009-2018. 1915 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 9304 records from Echinoderm collection of National Museum of Nature and Science. 54 records from Ompok platyrhynchus, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 109176 records from Herps Specimens. 39139 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 8 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 5 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 18 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 4 records from Two new Afrotropical genera of Scatopsidae (Diptera). 3689 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 6 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 292 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 1 records from Arthropoden aus südostalpinen Höhlen.. 5 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 4 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 289 records from bmhs_butterfly_collection. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 3 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 16 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 1139 records from SWECO. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 62628 records from EAC - Herbário Prisco Bezerra. 3 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 3 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1564 records from Leif Richardson Vermont Bee Specimens. 247 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 29102 records from Collection Crustacea - ZMB. 726 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 9 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 18 records from Peckoltia cavatica, a new loricariid catfish from Guyana and a redescription of P. braueri (Eigenmann 1912) (Siluriformes).. 1200 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 6 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 30 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 6 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 3 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 154 records from Dermaptera in the icipe collection. 1397 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 33 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 65 records from Three new species and new records of cuckoo bees of the genus Epeolus in Turkey (Hymenoptera: Apidae: Nomadinae). 73 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 11 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 51 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 16 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 1 records from Redescription of Parafronurus youi and generic affinities (Ephemeroptera, Heptageniidae, Ecdyonurinae). 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 12 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 23238 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 88 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 42 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 15 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 5 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 6859 records from Plan de vertebrados de la Patagonia. 10 records from Tribe Myrmeleontini (Neuroptera: Planipennia: Myrmeleontidae) in Iran. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 18 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 2 records from Myzostoma khanhkhoaensis (Myzostomida), a new myzostomid species from the Nhatrang Bay, Vietnam. 2 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 4 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 71 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 350 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 606 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 48 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 6977 records from 2019_NSMK_PL_2. 6579 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 1 records from Description of Pseudosteineria longisetis sp. n. from northeastern Brazil with a review of the genus Pseudosteineria Wieser, 1956 (Nematoda: Xyalidae). 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 36 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 30417 records from Collection Pisces SMF. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 7 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 4 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 534 records from MEXU/Tipos de plantas vasculares. 4 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 56 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 8 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 50 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 7 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 101 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 194 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 46933 records from Botanical Museum, Copenhagen, Mycology Herbarium. 2 records from A new species of Seira (Collembola: Entomobryidae) from northeastern Brazil. 3 records from One new species and new record of the leafhopper genus Watara Dworakowska from Thailand (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini). 9 records from Collection Myriapoda - SNSD. 55 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 1924 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 1 records from On two italian Lithobius species described by Silvestri with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda Lithobiidae). 30 records from Lacantunia enigmatica (Teleostei: Siluriformes) a new and phylogenetically puzzling freshwater fish from Mesoamerica.. 1 records from A new species of Stenampyx Karsch, 1890 from East Africa (Orthoptera: Tettigoniidae, Pseudophyllinae, Phyllomimini) - evidence of a former connection of West-Central and East African forests. 5 records from Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini. 78 records from Geographical and bathymetric distribution of mysids (Crustacea: Mysida) in the seas of the Iberian Peninsula. 1000 records from nsmk_mm_2019. 50 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 9 records from Morphological and molecular analyses confirm the occurrence of two sympatric Lysmata shrimp (Crustacea, Decapoda) in the southwestern Atlantic. 15 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 1 records from Studies in Australian Tettigoniidae: New Fully-winged Agraeciini From Northeastern Australia (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini). 1 records from A new species of Proneuronema (Neuroptera: Hemerobiidae) from late Eocene Rovno amber. 2 records from The discovery of Euryrhynchidae (Crustacea: Decapoda) in India, with the description of a new genus and species. 3 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 8 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 4 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 3974 records from DBL_Life. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 859 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 4 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 95 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 6 records from Systematic account of new Porifera (Demospongiae) records from the oceanic Island of Madeira (NE Atlantic). 1 records from Discovery of the transantarctic distribution of the genus Metanteon Olmi (Hymenoptera: Dryinidae), with description of a new species from New Caledonia. 3 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura: Diogenidae) from southern India. 2171 records from Thrips (Thysanoptera) in Norway. 3 records from A new species of Homo from the Late Pleistocene of the Philippines. 2 records from Deux nouvelles espèces d’ Aloe L. (Xanthorrhoeaceae, Asphodelaceae), section Lomatophyllum Rowley, de Madagascar. 613 records from Implementación de la bioindicación en el Río Cauca - 2016. 362 records from Mammalian Specimens of the Yamagata Prefectural Museum. 104 records from BID-Malawi-Arctiidae-Biodiversity-Data. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 89 records from Bird specimens of Ryukyu University Museum (Fujukan). 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 2 records from A new species of Eupariini from Eocene Baltic amber (Coleoptera: Scarabaeidae: Aphodiinae). 731 records from An updated record of Gaden Robinson's collection of Macro-moths of Fiji and Rotuma. 1483 records from Sistematización de la Colección Entomológica Forestal del CENID-COMEF. 451 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 5908 records from Colecção Entomológica do Museu de História Natural de Maputo. 18 records from Three new species of Labomimus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from Taiwan, China, with an updated key for L. shibatai Sawada-group. 3 records from Three new species of Elachistidae (Lepidoptera: Gelechioidea) from India. 2215 records from Collection Polychaeta - ZSRO. 21 records from Consolidated Checklist of Hard Corals of the Genus Acropora Oken, 1815 (Scleractinia: Acroporidae) in North Borneo, East Malaysia. 17 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 1 records from A new species of Eumeces Wiegmann 1834 (Sauria: Scincidae) from Iran. 132 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 2 records from A new species of Isthmura (Caudata: Plethodontidae) from the montane cloud forest of central Veracruz, Mexico. 2 records from Description of a new whiteflyı Pealius satakshiae Dubey (Hemiptera: Aleyrodidae) ı infesting Quercus leucotrichophora (Fagaceae) in the Western Himalayaı India. 3 records from A new species of phlebotomine sandfly, Pintomyia (Pifanomyia) duckei (Diptera: Psychodidae) from Manaus, State of Amazonas, Brazil. 17 records from Three new species of Tridentella Richardson, 1905 (Isopoda: Cymothoida: Tridentellidae) from New Caledonia. 4 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China. 437 records from SJRP-Fungi - Herbário de fungos de São José do Rio Preto. 31 records from Synonymies, a new combination, and four new species in Amphicnaeia Bates (Coleoptera: Cerambycidae: Lamiinae). 27 records from Aves de la expedición en lago de Tota, Boyacá - Proyecto Boyacá BIO. 4381 records from Gunma Museum of Natural History, Fungi Specimen. 38827 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 14 records from Eight new species of Ptenidiini and Discheramocephalini (Coleoptera: Ptiliidae) from Ecuador. 27 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 27192 records from Plant specimens of Horaiji-san Museum of Natural History Kichi T. collection. 1 records from A new brachypterous Filchneria and two new generic records for China, Arcynopteryx and Pictetiella (Plecoptera: Perlodidae). 3 records from Lectotypification of three species of Silene sect. Italicae (Rohrb.) Schischk. (Caryophyllaceae). 3 records from Three new species of the cutthroat eel genus Dysomma, with comments on the variation of D. taiwanense (Anguilliformes: Synaphobranchidae). 75 records from Species diversity of Myrmecofauna (Hymenoptera, Formicidae) on the southern slope of Djurdjura National Park (Northern Algeria). 5 records from The oribatid mite genus Topalia in Australia (Oribatida: Nosybeidae) and the taxonomic status of related families and genera. 5 records from Revision of Chimarrogale (Lipotyphla: Soricidae) from Vietnam with comments on taxonomy and biogeography of Asiatic water shrews. 3 records from Three new species of Entomobryoidea (Collembola: Entomobryomorpha) from Brazilian Caatinga-Cerrado transition, with identification keys to Brazilian Cyphoderus, Pseudosinella and Trogolaphysa species. 4583 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 11 records from New records of deep-sea shrimps of family Solenoceridae Wood-Mason & Alcock, 1891 (Crustacea: Decapoda: Dendrobranchiata) from Southwestern Atlantic. 187017 records from UWFC Ichthyology Collection. 8853 records from Auburn University Museum of Natural History Invertebrates. 17 records from Theropods of the Judith River Formation of dinosaur Provincial Park, Alberta, Canada. 1 records from Morphological and molecular distinction of two Fridericia species (Clitellata, Enchytraeidae) having same spermatheca type. 35 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 402 records from The ultor - group of the genus Dolichogenidea Viereck (Hymenoptera, Braconidae, Microgastrinae) from China with the descriptions of thirty-nine new species. 22501 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 16 records from Eight new species of the spider genus Khorata Huber, 2005 (Araneae: Pholcidae) from China. 3 records from A new genus and two new species of soft scale insect (Sternorrhyncha, Coccoidea, Coccidae) from Africa. 91253 records from CUMV Fish Collection. 50 records from A new genus and species of the family Symphysanodontidae, Cymatognathus aureolateralis (Actinopterygii: Perciformes) from Indonesia. 7 records from New Oligaphorura species (Collembola: Onychiuridae) from the forests of East Asia. 6922 records from MUST, Insecta. 2116 records from Collection entomologique Pierre Lachiver. 2 records from A taxonomic study on the Bornean and Philippines Sword-tailed Crickets in the genus Rhicnogryllus Chopard, 1925 (Orthoptera: Trgonidiidae; Trigonidiinae). 3 records from ZUEC-POP - Coleção de Polyplacophora do Museu de Zoologia da UNICAMP. 31 records from Stenus maculifer CAMERON: eine Büchse der Pandora (Coleoptera, Staphylinidae) 365. Beitrag zur Kenntnis der Steninen. 72252 records from University of Tennessee Fungal Herbarium. 167484 records from University of Michigan Museum of Zoology, Division of Mollusks. 4 records from Amphicnemis valentini sp. nov. from the Cardamom ecoregion in Cambodia and Vietnam (Odonata: Coenagrionidae). 2519 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 3 records from Review of the fossil record of Bittacomorphinae (Diptera: Ptychopteridae). 2103 records from Flora ficológica de la huasteca potosina. 2340 records from Type Specimen Database of Museum and Institute of Zoology PAS. 3784 records from Herbier de Wallis et Futuna. 75 records from Annotated type-catalogue of Brachyura (Crustacea, Decapoda) of the Muséum national d’Histoire naturelle, Paris. Part II. Gecarcinidae and Grapsidae (Thoracotremata, Grapsoidea), with an Appendix of pre- 1900 collectors. 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 112 records from Revision of Nearctic Paramyia Williston (Diptera: Milichiidae). 14 records from A new species of Streblospio (Polychaeta: Spionidae) from the northern Adriatic Sea (Mediterranean Sea). 17 records from Two amazing new species of treehoppers (Hemiptera: Membracidae) from Colombia: Calloconophora estellae sp. nov. and Problematode robertoi sp. nov.. 2 records from A new flower fly species of Cepa Thompson & Vockeroth (Diptera: Syrphidae) from the Valdivian evergreen forest hotspot, Chile. 9 records from New species of Tenebrionidae Latreille, 1802 (Coleoptera: Tenebrionoidea) from the Philippines. 500 records from Coleccion de helechos de la FML. 9 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 55 records from Highland biodiversity of Fanniidae (Insecta, Diptera): fourteen new species from the Andes and Central America. 6 records from Alburnus magnificus, a new species of bleak from the Orontes River drainage (Teleostei: Leuciscidae). 8 records from Endangered beauties: micro-CT cranial osteology, molecular genetics and external morphology reveal three new species of chameleons in the Calumma boettgeri complex (Squamata: Chamaeleonidae). 3 records from The spider genus Hersilia in Thailand, with descriptions of two new species (Araneae, Hersiliidae). 2 records from Anagrus turpanicus sp. n. (Hymenoptera: Mymaridae) from China, an egg parasitoid of Arboridia kakogowana (Hemiptera: Cicadellidae). 1 records from Physoschistura walongensis, a new species of loach (Teleostei: Nemacheilidae) from Arunachal Pradesh, northeastern India. 165 records from Tetrápodos de Uruguay. 4 records from Craspedotropis gretathunbergae, a new species of Cyclophoridae (Gastropoda: Caenogastropoda), discovered and described on a field course to Kuala Belalong rainforest, Brunei. 200 records from 2019_nsmk_mm_20200324. 3 records from Larval morphology and life history of Eutrichosoma mirabile Ashmead and description of a new species of Eutrichosoma (Hymenoptera, Chalcidoidea). 7 records from Three new species of the genus Mimetus Hentz, 1832 (Araneae: Mimetidae) from Yunnan-Guizhou Plateau of China. 2095 records from University of Kentucky Insect Collection. 7 records from Five new species in the genus Leschenaultia Robineau-Desvoidy, 1830 (Diptera: Tachinidae) from Mato Grosso, Mato Grosso do Sul and Rondônia, Brazil. 9 records from Six freshwater microturbellarian species (Platyhelminthes) in permanent wetlands of the Coastal Plain of southern Brazil: new records, abundance, and distribution. 2 records from A remarkable burrow-dwelling alpheid shrimp, new genus and new species, from the tropical eastern Pacific (Malacostraca: Decapoda: Caridea). 187 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 2 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica). 10 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 18224 records from K-State Museum of Entomological and Prairie Arthropod Research. 5 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 1 records from Discovery of a new species of Dryocosmus Giraud, 1859 (Hymenoptera: Cynipidae: Cynipini) on Castanopsis tibetana from China. 80 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 13 records from An annotated species list of regular echinoids from Sri Lanka with notes on some rarely seen temnopleurids. 1127 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 104 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 24795 records from Université d'Aix-Marseille. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 2068 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 25 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 36 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 22 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 23 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 5 records from Two new species of genus Lasiosina Becker from China (Diptera, Chloropidae). 11994 records from Hatikka Observation Database. 2433 records from UWYMV Bird Collection (Arctos). 1 records from Synopsis of the extinct Batrachia, Reptilia and Aves of North America. 19 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 2020 records from Birds (NHMK-BI). 3 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 2 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 7 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 11 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 298 records from New data on species diversity of Annelida (Oligochaeta, Hirudinea) in the Kharbey lakes system, Bolshezemelskaya tundra (Russia). 134 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 6 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 4 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 5780 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 50 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 1275 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 1 records from A new genus of giant lacewing (Insecta, Neuroptera, Ithonidae) from the Middle Jurassic of China. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 26 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 32916 records from Insect specimen database of Atsugi City Museum. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 123060 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 3 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 30 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 5410 records from Collection ornithologique A. Maës. 5 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 2 records from New Entodiniomorphid Ciliates, Buetschlia minuta n. sp., B. cirrata n. sp., Charonina elephanti n. sp., from Asian Elephants of Turkey. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 89 records from Mammal specimens of Komatsu City Museum. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 3 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 1490 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 11208 records from Natural History Museum Rotterdam (NL) - Chordata collection. 12 records from Mamíferos del municipio de Santa Bárbara, Santander - Proyecto Santander BIO. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 406575 records from Herbarium of Taiwan Forestry Research Institute. 37 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 5 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 3 records from New Notophthiracarus species (Acarina, Oribatida, Phthiracaridae) and overview of the distribution of the genus in South Africa. 7066 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 258 records from Malawi-Histeridae-Biodiversity-Data. 25374 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 4439 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 29 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 1 records from Schistura alboguttata, a new loach species of the family Nemacheilidae (Pisces: Cypriniformes) from the Pearl River basin in Guangxi, South China. 3 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 12 records from Rotundocoris, a new apterous genus of Carventinae from China (Heteroptera: Aradidae). 26 records from The genus Semicerura (Collembola; Isotomidae) in Asia. 1 records from Oribates calcaratus. 499880 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 115 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 96 records from The species of the genus Diaclina Jacquelin du Val (Coleoptera: Tenebrionidae: Alphitobiini) from Sub-Saharan Africa. 1000 records from Axel W. Erikssons African Bird Collection at Vänersborg Museum. 1900 records from Carabidae of the European North-East of Russia. 5327 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 4019 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 9997 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 35 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 52 records from Pelvicachromis signatus and Pelvicachromis rubrolabiatus, two new cichlid species (Teleostei, Perciformes) from Guinea, West Africa.. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 29137 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 41 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 5462 records from Arachnids (Aranei, Opiliones) from grass stand and forest litter in the Urals, Russia. 27 records from Ground spiders (Araneae: Gnaphosidae, Liocranidae, Prodidomidae) from the Greek islands Rodos, Symi and Karpathos, with the description of new species. 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 228 records from Bishop's University Insect Collection (BUIC). 16 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 47 records from Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae). 135839 records from BioFokus. 6 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 71494 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 104 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 4 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 8649 records from Fossil (WSHN-FO). 4 records from Two new genera and species of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae) and redescription of the type species of Paraidioscopus. 7 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 7 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 14 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 7 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 13 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 425 records from Collection de C.C.H. Jongkind aux Monts Nimba. 281 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 5 records from A new Brazilian species of Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorinae), a predator of Tinocallis kahawaluokalani (Kirkaldy) (Hemiptera, Aphididae). 26 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 4 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 13 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 14 records from Laetosphecia, a new genus of clearwing moths from south-eastern China, with a brief review of the Sesiini from China (Lepidoptera, Sesiidae). 8 records from A review of the ant genus Metapone Forel from Madagascar.. 6 records from Mammalia (JNHM-MM). 13940 records from The Vascular Plants Collection of the University of Goettingen. 10 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 2120 records from Flora vascular acuática de la cuenca del Río Tamesí. 59 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 54 records from The bee Ruizanthedella mutabilis Spinola (Hymenoptera: Halictidae): a very common but poorly known species studied using integrative taxonomy. 13 records from A new genus and two new species of miniature clingfishes from temperate southern Australia (Teleostei, Gobiesocidae). 1 records from Larval morphology of Plagiosterna adamsii (Baly) and P. aenea (Linnaeus) with resurrection of Gastrolinoides Chûjô & Kimoto and P. formosana (Bates) (Coleoptera: Chrysomelidae: Chrysomelinae). 5 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 5 records from Two new nematode species of the genus Tobrilus Andrássy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 9 records from New data on brown lacewing genus Wesmaelius Krüger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species. 10509 records from Andes to Amazon Biodiversity Program. 5327 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 665 records from Collection Echinodermata - ZMB. 443 records from Inventario herpetofaunístico del noroeste de Hidalgo. 739 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 3 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 25 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 12 records from Update of the genus Leptochiton (Mollusca: Polyplacophora) in Chilean deep waters: three new reports and description of two new species. 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 13 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano. 8 records from A taxonomic review of the genus Triscaedecia (Lepidoptera: Alucitidae) in the world fauna. 4 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 11 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 2326 records from Jardín Botánico Atlántico, Gijón: JBAG. 1 records from Description of a new species of the Ponerine ant genus, Emeyopone (Hymenoptera: Formicidae) from Karnataka, India.. 1 records from A new species of Rock Gecko of the genus Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from Belitung Island, Indonesia. 32706 records from UAM Bird Collection (Arctos). 16 records from A new species of chimaeroid, Hydrolagus alphus sp. nov. (Chimaeriformes: Chimaeridae) from the Galapagos Islands.. 2 records from Description of Metarhabditis giennensis sp. n. (Nematoda, Rhabditida, Rhabditidae) from decaying wood of a riverbank forest in the southern Iberian Peninsula. 3 records from New species and two new records of Erythroneurini from China (Hemiptera Cicadellidae, Typhlocybinae). 6 records from Two new species of Loboschiza from Cambodia and Vietnam (Lepidoptera: Tortricidae: Olethreutinae: Enarmoniini). 1698 records from UTEP Herpetology Osteology (Arctos). 3 records from New Earwigs in Protodiplatyidae (Insecta: Dermaptera) from the Middle Jurassic Jiulongshan Formation of Northeastern China. 2 records from Revision of the tree crickets of China (Orthoptera: Gryllidae: Oecanthinae). 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 13 records from Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae). 11 records from Tanytarsini (Diptera: Chironomidae) from madicolous habitat in Southeast Brazil: new species and new records. 41 records from Taxonomy of Tabanus trivittatus species-group (Diptera: Tabanidae), with description of five new species. 1 records from Acmaeodera (Ptychomus) kubani sp. n. from Northern Africa and the Arabian Peninsula, with notes on the taxonomic composition of the subgenus Ptychomus Marseul, 1866 (Coleoptera: Buprestidae: Polycestinae: Acmaeoderini). 9 records from Four new species of Epacanthion Wieser, 1953 (Nematoda: Thoracostomopsidae) in intertidal sediments of the Nanji Islands from the East China Sea. 398 records from Tsetse flies of East Africa update. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 3682 records from Flora of Sumatra : Vascular plant collection from Batang Toru Forest deposited in ANDA Herbarium. 387 records from Distribución espacio-temporal de las larvas de atunes en el Golfo de Tehuantepec, México. 1 records from Amphibia ZMK. 4 records from A new species of Heliothrips (Thysanoptera, Panchaetothripinae), based on morphological and molecular data. 8 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 3 records from Redescription of Zoica puellula (Simon, 1898) (Araneae: Lycosidae: Zoicinae) and transfer of Zoica harduarae (Biswas & Roy, 2008) to Agelenidae C. L. Koch, 1837. 20755 records from pins. 3 records from A new species of Notomulciber (Micromulciber) Aurivillius, 1913, from the southern Western Ghats of India (Coleoptera: Cerambycidae: Lamiinae: Homonoeini). 1005 records from Collection Crustacea - KAUMM. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 12 records from Revision of the genus Kailasha (Lepidoptera, Erebidae, Arctiinae) from Oriental region, with description of one new species. 772 records from FBIP: Baboon spider distribution records from selected South African museums. 1 records from Two new species of Xyalidae (Monhysterida, Nematoda) from the East China Sea. 40 records from A review of the leafhopper genus Scaphoideus (Hemiptera: Cicadellidae: Deltocephalinae) from Guangxi of China, with description of one new species. 3 records from A new species of the genus Thrips (Thysanoptera: Thripidae) from the Western Ghats of India. 2509 records from Colección de Oligoquetos Acuáticos de la UPV/EHU. 49 records from Mammal specimens of Natural History Museum, Kishiwada City. 381 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 12 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 55849 records from UWBM Mammalogy Collection (Arctos). 4 records from A new species of Pselaphogenius Reitter, 1910 of the fiorii species group from southern Italy (Coleoptera, Staphylinidae, Pselaphinae). 2 records from Acromyrmex charruanus: a new inquiline social parasite species of leaf-cutting ants. 11129 records from Royal Ontario Museum Fungarium (TRTC). 16 records from Cytheroid ostracods (Crustacea) from South Korea, with description of a new species. 10 records from Five new species of genus Encarsia Förster from China (Hymenoptera: Aphelinidae). 260 records from osac_oarisma. 174716 records from Vascular plant herbarium, Tromsø Museum. 5 records from Minjerribah (Diptera: Dolichopodidae), a new genus from coastal Queensland, Australia. 26 records from Terre d'huiles. 14165 records from NYSM Mammals. 7 records from Lost species in Cameroon: rediscovery of the endangered freshwater crab, Louisea balssi (Bott, 1959) (Brachyura: Potamonautidae), with notes on its ecology and conservation. 2067 records from Base de datos de la familia Cactaceae de la Península de Baja California, México. 37839 records from Fiocruz/CEIOC - Coleção Entomológica do Instituto Oswaldo Cruz. 62171 records from Canadian Museum of Nature Fish Collection. 59050 records from JPB - Herbário Lauro Pires Xavier. 166 records from A revision of the spider genus Zaitunia (Araneae, Filistatidae). 6 records from On four new species of the jumping spider genus Mago O. Pickard-Cambridge, 1882 from South America (Araneae: Salticidae). 130 records from Endemic earthworms (Oligochaeta: Lumbricidae) of the Balkan Peninsula: a review. 6 records from A new species of Uvarus Guignot, 1939 (Coleoptera: Dytiscidae: Hydroporinae: Bidessini) from Florida, USA. 1200 records from 2019_mjim_in. 2 records from A new species of Behningia Lestage, 1929 (Ephemerotera: Behningiidae) from China. 213 records from Revision of Netomocera Bouček (Hymenoptera: Chalcidoidea: Pteromalidae), excluding the Oriental species. 8 records from Pomacentrus aurifrons, a new species of damselfish (Pomacentridae) from Melanesia.. 5042 records from Tracheophyta collection of Biodiversity Center of Japan, Ministry of the Environment. 10 records from Sand wasp (Hymenoptera: Crabronidae) parasites emerging from mud wasp nests (Hymenoptera: Sphecidae) - a reliable host record of Thraxan Yeates & Lambkin (Diptera: Bombyliidae: Anthracinae) with description of the pupal exuviae of three Thraxan species. 122590 records from Field Museum of Natural History (Botany) Bryophyte Collection. 31173 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 2 records from A new micropterous species of the genus Spathius Nees (Hymenoptera: Braconidae: Doryctinae) from the North Eastern Himalayas, India. 14 records from What is Pseudopotamilla reniformis (Sabellidae)? Comparisons of populations from Britain, Iceland and Canada with comments on Eudistylia and Schizobranchia. 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 16 records from Resurrection of Caltoris ranrunna (Sonan) from synonymy as a skipper endemic to Taiwan based on COI barcode and morphology. 29 records from A review of the arboreal Afrotropical ant genus Axinidris.. 24 records from Bombus impatiens Cresson (Hymenoptera: Apidae, Apinae, Bombini) from the Prairies Ecozone in Canada. 161 records from Diversity and distribution of Pleioplectron Hutton cave wētā (Orthoptera: Rhaphidophoridae: Macropathinae), with the synonymy of Weta Chopard and the description of seven new species. 92374 records from Herbarium of University of Coimbra (COI ). 268 records from Biodiversidad en las propuestas para declaratoria de Áreas Protegidas en los Municipios de Dagua, Restrepo, La Cumbre y Vijes y un Grupo de Reservas Naturales de la Sociedad Civil. 1127 records from ioj_hemiptera_collection. 1 records from Arthropoden aus südotsalpinen Höhlen gesammelt von Karl Strasser. 4. Aufsatz. 3 records from Taxonomy of the Sand Sliders of Western Australia’s central coast (genus Lerista, Squamata: Scincidae): recognition of Lerista miopus (Günther, 1867). 2452 records from Plantas de la expedición al Río Apaporis - Proyecto Colombia BIO. 4 records from New species and records of the Pericoma trifasciata group from Croatia (Diptera: Psychodidae). 2 records from Studies on the ant fauna of Melanesia V. The tribe Odontomachini.. 26 records from Revision of the genus Celebargiolestes Kennedy, 1925 (Odonata: Argiolestidae). 11 records from Notes on the Rhyacophila angulata Species Group with descriptions of two new species (Insecta, Trichoptera, Rhyacophilidae). 1 records from Resolving the taxonomic puzzle of Boana cinerascens (Spix, 1824), with resurrection of Hyla granosa gracilis Melin, 1941 (Anura: Hylidae). 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 9 records from Study of Laemostenus species across Zagros and Central zone of Iran, with the description of seven new cavernicolous species and notes on subgenus Iranosphodrus (Coleoptera: Carabidae: Sphodrini). 5 records from Two new species of Pristimantis (Anura: Craugastoridae) with notes on the distribution of the genus in northeastern Colombia. 10 records from Integrative taxonomy reveals two sympatric species of the genus Eucriotettix Hebard, 1930 (Orthoptera: Tetrigidae). 88 records from Revision of the genera Pareuthria Strebel, 1905, Glypteuthria Strebel, 1905 and Meteuthria Thiele, 1912 (Gastropoda: Buccinulidae) with the description of three new genera and two new species from Southwestern Atlantic waters. 92411 records from UPCB - Herbário do Departamento de Botânica. 186 records from Taxonomic revision of the South American subgenus Canthon (Peltecanthon) Pereira, 1953 (Coleoptera: Scarabaeidae: Scarabaeinae: Deltochilini). 5 records from Notes on the genus Yunnantettix Zheng (Tetrigidae: Cladonotinae), with descriptions of two new species from Thailand. 11 records from A new species of Probolomyrmex from Madagascar.. 951 records from Poliquetos invasores (Annelida: Polychaeta) del Puerto de Mazatlán, Sinaloa. 2 records from A revision of the genus Conocrinus d’Orbigny, 1850 (Echinodermata, Crinoidea, Rhizocrinidae) and its place among extant and fossil crinoids with a xenomorphic stalk. 44 records from Contributions to the taxonomy, identification, and biogeography of the Western Palaearctic species of Campoletis Förster (Ichneumonidae: Campopleginae). 9 records from Lethrus (Lethrus) thracicus (Coleoptera: Geotrupidae), a new species from the European part of Turkey. 7357 records from ZFMK Coleoptera collection. 10 records from Philippines National Museum Birds Collection. 36169 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 13 records from On some lesser known sea cucumbers in the Natural History Museum, UK (Echinodermata: Holothuroidea). 94 records from Review of selected species of Campsurus Eaton 1868 (Ephemeroptera: Polymitarcyidae), with description of eleven new species and a key to male imagos of the genus. 2 records from A new genus and species of Acaenitini (Hymenoptera, Ichneumonidae, Acaenitinae) from China. 18 records from Integration of molecular, bioacoustical and morphological data reveals two new cryptic species of Pelodytes (Anura, Pelodytidae) from the Iberian Peninsula. 151 records from Revision of the genus Odocnemis Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from Turkey, the Caucasus and Iran with observations on feeding habits. 10 records from Kartlegging av kortdistansespredning av fremmede bartrær - Helgelandskysten. 3 records from A new species of Angaeus from Malaysia with possible affinity to related genera within Stephanopinae (Araneae: Thomisidae). 7 records from Microcambeva ribeirae sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new sarcoglanidine catfish from the Rio Ribeira do Iguape basin, southeastern Brazil.. 2 records from A new species of Rhaptopetalum (Lecythidaceae) from south-western Gabon. 15 records from Two new enigmatic species of the genus Merodon Meigen (Diptera: Syrphidae) from the north-eastern Middle East. 139 records from Review of the genus Eburodacrys White, 1853 (Coleoptera: Cerambycidae: Cerambycinae). 13 records from Cnidarian Specimens of the Yamagata Prefectural Museum. 4 records from Two new species of Flavoperla (Plecoptera: Perlidae) from Shaanxi Province of China. 10 records from Revision of the spider crab genus Sargassocarcinus Ward, 1936 (Crustacea: Brachyura: Epialtidae). 451 records from Caracterización biológica de la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia. 1 records from Nothrus biciliatus. 21 records from On the taxonomic position of Phaenomenella Fraussen & Hadorn, 2006 (Neogastropoda, Buccinoidea) with description of two new species. 2 records from Arthropoden aus südostalpinen Höhlen.. 4 records from A new lacewing species of the Chrysoperla carnea species-group from central Asia associated with conifers (Neuroptera: Chrysopidae). 3 records from A new species of the alpheid shrimp genus Thuylamea Nguyên, 2001 (Crustacea: Decapoda: Caridea) from Yatsushiro Sea, Kyushu, Japan. 7 records from Voragocoris weirauchae sp. n. (Heteroptera: Schizopteridae: Schizopterinae), a further minute litter bug species from Brazil. 8 records from Cirrhigaleus australis n. sp., a new Mandarin dogfish (Squaliformes: Squalidae) from the south-west Pacific.. 143920 records from NINA insect database. 10075 records from Nematoda of Costa Rica (INBio). 75 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 554 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 396164 records from South Australian Museum Australia provider for OZCAM. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 25 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 148 records from Herbarium BSG Hepaticopsida. 20 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 100 records from Brock University Herbarium (BU). 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 309 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 128 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 78 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 5 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 38 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 20 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 9 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 41 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 15 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 35 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 887 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 3627 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 95 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 2 records from Mormolyce matejmiciaki sp. nov. (Coleoptera: Carabidae: Lebiinae) from Borneo. 99749 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 2899 records from University of Sindh Jamshoro Herbarium. 6 records from New Galumnoidea (Acari, Oribatida) from Hanoi (Northern Vietnam). 48 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 2 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 1 records from A complementary description of the male of Kyphopteryx yangi (Plecoptera: Taeniopterygidae) from China. 76 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 41 records from Registros Primates Neotropicales Convocatoria APC. 16 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 19 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 4 records from Cribrilinids (Bryozoa, Cheilostomata) associated with deep-water coral habitats at the Great Bahama Bank slope (NW Atlantic), with description of new taxa. 3 records from Two new scale insect species (Hemiptera: Coccomorpha: Acanthococcidae and Pseudococcidae) and a new country record from protected areas in Iran. 43 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna”. 1 records from Hoplophora ardua. 14 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 7128 records from La familia Asclepiadaceae en México. 18 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 17 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 34 records from Morphological examination and phylogenetic analysis clarify the taxonomic status of Cuban Longior Travassos & Kloss, 1958 (Nematoda: Thelastomatoidea: Hystrignathidae). 52 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 1 records from Redescription of Favognathus insularis (Luxton) (Acari: Trombidiformes: Cryptognathidae) from Brazil, with a key to the world species of Favognathus. 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 43 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 8 records from Taxonomy and diversity of coelobite bryozoans from drift coral cobbles on Co To Island, northern Vietnam. 54 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 49 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 4 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 30004 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1 records from Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 50 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 82 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 8462 records from University Of Pretoria: Lacewing Database Project (1911-2015). 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 4400 records from USAC Mammals Collection. 3 records from A new mayfly species of Rhoenanthus (Ephemeroptera: Potamanthidae) from Peninsular India. 20 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 3399 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 363 records from PSUZC-Reptile Collection. 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 1402 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 70 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 59 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 1 records from First columbellid species (Gastropoda: Buccinoidea) from deep-sea hydrothermal vents, discovered in Okinawa Trough, Japan. 89 records from The Dragon-flies (Odonata) of Palestine, based primarily on collection made by Dr. P. A. Buxton, with Notes on the Species of the Adjacent Regions.. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 38 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 5926 records from Collection Echinodermata SMF. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 5020 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 4 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 49341 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 1 records from The Genus Episynlestes Kennedy (Odonata: Synlestidae). 124 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 480 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 5 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 1 records from Oribates fusifer. 4 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 4 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 24 records from Paracobitis abrishamchiani, a new crested loach from the southern Caspian Sea basin (Teleostei: Nemacheilidae). 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 2 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 7 records from A new species of Catomus Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from the Aeolian archipelago (Sicily, Italy). 75 records from Nemertini - SMF. 5 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 57 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 3 records from A new species of frog (genus Eleutherodactylus) from a cloud forest in Western Colombia. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 3 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 7 records from Sangpradubina, an astonishing new mayfly genus from Thailand (Ephemeroptera: Leptophlebiidae: Atalophlebiinae). 8 records from New and little-known crickets from Southern Guangxi, China (Orthoptera: Grylloidea: Gryllidae: Phalangopsidae; Trigonidiidae). 3 records from A new species of Caligus Müller, 1785 (Copepoda: Siphonostomatoida: Caligidae) from coral reef plankton in the Mexican Caribbean. 36 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 4 records from A new genus and species of Stigmoderini Lacordaire, 1857 (Coleoptera: Buprestidae: Buprestinae) from Southeast Brazil with notes on its hypothesized mimicry complex. 1764 records from Arachnida of Costa Rica (INBio). 20 records from Revision of the Melanogaster jaroslavensis group (Diptera: Syrphidae), with description of a new species from Afghanistan. 205 records from Occurrence of some antimalarial plants from Cameroon. 33 records from New gnathiid isopod crustaceans (Cymothoida) from Heron Island and Wistari Reef, southern Great Barrier Reef. 3 records from Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear. 26 records from New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon. 24 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 8 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 1825 records from Galathea II, Danish Deep Sea Expedition 1950-52. 1 records from The Crushing Bite of Tyrannosaurids. 12497 records from NCSM Non-molluscan Invertebrates Collection. 111529 records from The AAU Herbarium Database. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 6 records from Two new species of deeper dwelling Apogon (Perciformes: Apogonidae) from Micronesia and South Pacific Ocean.. 8 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 17 records from The Neotropical species of Clistopyga (Hymenoptera, Ichneumonidae, Pimplinae). Part II: the C. isayae species group, with the description of seven new species. 3 records from A new spider species of the genus Sudharmia from Sumatra, Indonesia (Araneae, Liocranidae). 9 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Daniel Piechowski. 79 records from Review of the subtribe Gyrophaenina Kraatz 1856 (Coleoptera: Staphylinidae: Aleocharinae: Homalotini) of Middle Asia, with emphasis on the fauna of Kazakhstan. 3 records from Immature stages of the genus Casignetus MacLeay, 1819 (Coleoptera: Lucanidae: Lucaninae). 448 records from Three new Eustala (Araneae, Araneidae) species from the Galápagos Islands (Ecuador). 100 records from orstom_macassar_corindon_1980. 20 records from Description of a new species of the genus Caeneressa from China, with a checklist of the genus (Lepidoptera: Erebidae). 48671 records from Lichen herbarium TRH, NTNU University Museum. 3 records from Ceropsylla pouteriae Burckhardt sp. nov. (Hemiptera: Psylloidea: Triozidae) ı a new species of jumping plant-louse inducing galls on the leaves of Pouteria ramiflora (Mart.) Radlk. (Sapotaceae): taxonomyı gall structure and histochemistry. 11 records from First record of ectoparasitic ciliates, of genus Trichodina (Ciliophora: Trichodinidae) parasiting cultured Oranda Gold Fish (Carassius auratus auratus L.) in India. 61 records from A taxonomic revision of the catshark genus Holohalaelurus Fowler 1934 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae), with descriptions of two new species.. 1475 records from Collembola of forested tundra in Vorkuta surroundings (1978-1979 and 1985). 126 records from A revision of the endemic South African long-jawed ground spider genus Drassodella Hewitt, 1916 (Araneae: Gallieniellidae). 19 records from Jewel beetles (Coleoptera, Buprestidae) collected during the 2018 field survey on Iejima Island, the Okinawa Islands, Ryukyus, south-western Japan. 69 records from A new East African genus of spirostreptid millipedes (Diplopoda, Spirostreptida, Spirostreptidae), with notes on their fungal ectoparasite Rickia gigas. 2088 records from Actualización de la base de datos de helmintos parásitos de peces de agua dulce de México. 3076 records from Distribución geográfica de las lagartijas partenogenéticas del género Aspidoscelis en México. 1 records from Crenicichla ploegi, a new species of pike-cichlid of the C. saxatilis group from the Rio Juruena and upper Rio Paraguai basins in Brazil, with an updated diagnosis and biogeographical comments on the group (Teleostei: Cichlidae). 3 records from Comparative phylogeography of bamboo bats of the genus Tylonycteris (Chiroptera, Vespertilionidae) in Southeast Asia. 10234 records from Collection entomologique Barthélémy. 2 records from A new Pararistolochia Hutch. & Dalziel (Aristolochiaceae) from the Beanka Tsingy (western Madagascar). 5 records from New genus of the subfamily Oscinellinae from Brazil (Diptera: Chloropidae). 7331 records from Base de datos de las pteridofitas del estado de Veracruz, México. 2 records from Extending rarity: discovery of the rare braconine genus, Carinibracon van Achterberg (Hymenoptera: Braconidae) in the Oriental region with the description of a new species from south India. 15 records from On unreported historical specimens of marine arthropods from the Solnhofen and Nusplingen Lithographic Limestones (Late Jurassic, Germany) housed at the Muséum national d’Histoire naturelle, Paris. 12 records from A contribution to the Mutillidae (Hymenoptera) of Hong Kong. 3 records from Heizmannia rajagopalani n. sp. (Diptera: Culicidae) in Kerala, India, a species previously misidentified as Hz. metallica (Leicester). 13621 records from ZFMK Orthopteroidea collection. 7 records from Review of the leafhopper genus Stirellus Osborn & Ball, 1902 (Hemiptera: Cicadellidae: Deltocephalinae) with description of two new species from Pakistan. 2 records from A new Schistura from the Salween basin in western Yunnan (Teleostei: Nemacheilidae). 2 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 702 records from HSU Vertebrate Museum Reptile Collection. 18 records from Opheliidae (Annelida: Polychaeta) from the western Pacific islands, including five new species. 591 records from Avifauna de la reserva de la biosfera El Cielo, Tamaulipas, México. 6 records from A new species of Curculionichthys (Siluriformes: Loricariidae) from the north edge of the Brazilian Shield, lower Amazon basin. 4 records from Two new species of the genus Reticuluma Cheng & Li (Hemiptera: Cicadellidae Deltocephalinae: Penthimiini) from China. 5 records from Taxonomic revision of Phascogale tapoatafa (Meyer, 1793) (Dasyuridae; Marsupialia), including descriptions of two new subspecies and confirmation of P. pirata Thomas, 1904 as a ‘ Top End’ endemic. 7 records from Additions to the Genus Phyllodesmium, with a Phylogenetic Analysis and its Implications to the Evolution of Symbiosis. 6 records from Re-description of Orchestia stephenseni Cecchini, 1928: designation of neotype and senior synonym to Orchestia constricta A. Costa, 1853 (Crustacea: Amphipoda: Talitridae) by Reversal of Precedence. 5890 records from Rutgers University, Chrysler Herbarium - Macroalgae Collection. 689 records from BioBlitz Barcelona 2010-14. 43 records from Revision of the Agrilus gratiosus species-group (Coleoptera, Buprestidae, Agrilinae). 2 records from Review of subterranean Quedius, with description of the first hypogean species from the Russian Far East (Coleoptera: Staphylinidae: Staphylinini). 126 records from Bryological collection of Yugra State University. 21 records from Revision of the species related to Lalagetes subfasciatus Boheman and transfer of remaining Lalagetes species to other genera of Embrithini (Coleoptera: Curculionidae: Entiminae). 27 records from Bemerkenswerte Faltenwespen aus der äthiopischen Region. Teil 14 (Hymenoptera, Vespidae, Eumeninae). 5 records from Ecological Guild Evolution and the Discovery of the World’s Smallest Vertebrate. 41100 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 798 records from Computarización de la Colección de Referencia de Nemátodos Fitopatógenos del Centro Nacional de Referencia Fitosanitaria de la Dirección General de Sanidad Vegetal. 22 records from Taxonomic review of the plant bug subfamily Isometopinae for Taiwan and Japanese Southwest Islands, with descriptions of new taxa (Hemiptera: Heteroptera: Miridae: Isometopinae). 13 records from New records of mosquitoes (Diptera: Culicidae) found in phytotelmata in Northern Argentina. 88 records from P. W. Lund collection in the National History Museum of Denmark, Copenhagen. 7 records from Contribution to the Mesochorinae (Hymenoptera, Ichneumonidae) of Nepal. 59 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 31 records from Two new species of the genus Narcotica Sugi, 1982 (Lepidoptera: Noctuidae: Acronictinae). 1667 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 649 records from Beetles from nature reserves and nearby forests in Østmarka. 40 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera Oecophoridae) V. The unistriatella species group, with descriptions of seven new species. 4975 records from Radiolaria specimens from the Norwegian Sea and Arctic Ocean. 19 records from Distribution Data for Megachile chomskyi. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 175 records from A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 3. Revision of the Craspedophorus strachani and C. brevicollis groups (Coleoptera: Carabidae). 3 records from A new species of Xiphogramma Nowicki (Hymenoptera: Chalcidoidea) from Saudi Arabia. 597 records from Eriophyoid Mites of Poland. 2 records from Neotype Designation for Aedes (Stegomyia) albopictus (Skuse). 5 records from On the genus Aphaobius Abeille de Perrin, 1878, with description of a new species from the mesovoid shallow substratum (MSS) of Austria (Coleoptera: Leiodidae: Cholevinae: Leptodirini). 1 records from Taxonomic re-evaluation of the monotypic genus Pararhabdophis Bourret, 1934 (Squamata: Colubridae: Natricinae) with discovery of its type species, P. chapaensis, from China. 855 records from Museu_Paraense_Emilio_Goeldi_Microfosseis_Collection. 1 records from On the Chilopoda from Turkey. 3 records from A new species of Gymnophthalmus (Squamata: Gymnophthalmidae) from sand dunes of the Llanos of Apure, Venezuela. 6 records from New Species of Neotibilis Grazia & Barcellos (Hemiptera: Pentatomidae: Pentatomini). 407 records from Systematics, biogeography and host-plant relationships of the Neotropical jumping plant-louse genus Russelliana (Hemiptera: Psylloidea). 1333 records from Sistematización de la colección de peces del centro de México. 2 records from Two new species of Batoctenus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from French Guiana. 446 records from Estudio ecológico-florístico de los enclaves de vegetación xerofítica inmersos en una selva baja caducifolia en el Istmo de Tehuantepec, Oaxaca. 62125 records from UCLA Donald R. Dickey Bird and Mammal Collection. 38 records from Description of the male of Cybaeodamus lycosoides (Nicolet), with new distributional data for C. meridionalis Lise, Ott & Rodrigues (Araneae, Zodariidae). 13 records from Two new species and a key to the dustywings of Mexico (Neuroptera, Coniopterygidae). 3062 records from University of Vermont, Pringle Herbarium, Algae Collection. 26 records from Further revision of the genus Bythotrephes Leydig (Crustacea: Cladocera: Onychopoda): redescription of B. brevimanus Lilljeborg, reevaluation of B. cederströmii Schödler, and description of a new species of the genus. 2 records from Contribution to the knowledge of Himalayan and North Indian species of Scaphidium (Coleoptera, Staphylinidae). 61 records from The Onthophagus fuscus (Coleoptera: Scarabaeidae) species complex: an update and the description of a new species. 9189 records from Plant specimens of Obihiro Centennial City Museum. 3 records from Two new Mesenchytraeus species (Annelida: Clitellata: Enchytraeidae) from Changbai Mountain, China. 7 records from Two New Species of Composetia (Annelida: Nereididae) from Small Estuaries in the Ryukyu Islands, Southern Japan, with a List of All Species Currently Belonging to Composetia. 3 records from A new species of highland vampire crab (Crustacea: Brachyura: Sesarmidae: Geosesarma) from Serian, Sarawak. 93 records from Benthic Foraminifera from the Capricorn Group, Great Barrier Reef, Australia. 33403 records from Colección de Entomología del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 5 records from Revalidation of a moray eel, Gymnothorax mucifer Snyder, 1904 (Teleostei: Anguilliformes: Muraenidae), with a revised distribution. 12351 records from SMDB - Santa Maria Departamento de Biologia. 3 records from New species of Myrmicine ants from Western Australia (Hymenoptera: Formicidae). 6 records from Review of the enigmatic genus Boalda with transfer of pulcherrima Köhler from Nephelistis and description of two new species (Lepidoptera: Noctuidae). 1 records from A New Species Of The Genus Liophloeothrips (Thysanoptera, Phlaeothripidae) From Iran. 13981 records from Flora of the Korean Peninsula. 235 records from Visual Plants (144.41.33.158) - Plants from Costa Rica; Helmut Dalitz. 3 records from Notioperilitus gen. nov., a new braconid genus (Hymenoptera: Braconidae: Euphorinae) from Australia, parasitoid of adult Morabinae (Orthoptera: Eumastacidae), with remarks on the generic placement of two Afrotropical euphorine species. 159 records from Pheidole (Hymenoptera, Formicidae) of Middle American Wet Forest. 3 records from Two new species and the molecular phylogeny of eight species of Macrostomum (Platyhelminthes: Macrostomorpha) from southern China. 23 records from New species of the genus Aztecatopse Haenni & Huerta from Mexico (Diptera, Scatopsidae). 1562 records from Plathelminthes - SMF. 13483 records from Insect specimens of Rikuzen-Takata City Museum. 4 records from Re-visiting the Aphidius urticae s. str. group: re-description of Aphidius rubi Starý and A. silvaticus Starý (Hymenoptera: Braconidae: Aphidiinae). 356 records from Amphibia Collection of Museum and Institute of Zoology PAS. 864 records from Caracterizando la diversidad de especies con códigos de barras del ADN en un grupo de avispas parasitoides: un caso de estudio en un área natural protegida mexicana. 18 records from A new species of Cintaroa from India and new records of Craspedophorus from Pakistan and the Philippines (Coleoptera: Carabidae: Panagaeini). 125 records from Review of the genus Meganola Dyar, 1898 (Lepidoptera: Nolidae, Nolinae) from Korea, with the description of a new species. 21794 records from Bryophyte specimens database of Mr. Tsutomu Kodama collection. 1 records from The cumacean genus Iphinoe (Crustacea: Peracarida) from Italian waters and I. daphne n. sp. from the northwestern Adriatic Sea, Mediterranean. 2 records from A new tropical montane firefly genus and species, active during winter and endemic to the southeastern Atlantic Rainforest (Coleoptera: Lampyridae). 18940 records from Cowan Tetrapod Collection - Mammals. 1818 records from Actualización de la información sobre los maíces criollos de Oaxaca. 34 records from The lestevoides species group of the genus Geodromicus Redtenbacher, 1857 (Insecta: Coleoptera: Staphylinidae: Omaliinae). 205 records from Bark and Ambrosia Beetles of Vermont from Thomas H. Atkinson. 2 records from The fungus-growing ant genus Apterostigma in Dominican amber.. 146 records from The genus Sicoderus Vanin 1986 (Coleoptera: Curculionidae: Curculioninae: Erodiscini) in the West Indies. 2 records from Zorotypus weiweii (Zoraptera: Zorotypidae), a new species of angel insects, from Sabah, East Malaysia. 13 records from Papuacocelus papuanus n. gen., n. sp. a new Eurycanthinae from Papua New Guinea, with notes on the genus Dryococelus Gurney, 1947 and description of the egg (Phasmatodea: Phasmatidae: Eurycanthinae). 9 records from A new troglobitic Tychobythinus from Sicily (Coleoptera, Staphylinidae, Pselaphinae). 2707 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 86 records from UWIZM Cnidarians. 119 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 1059 records from irregularia_mexico. 280 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 12776 records from Carabid Collection (Pinned Vouchers). 40339 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 152102 records from Tasmanian Museum and Art Gallery provider for OZCAM. 968 records from TTRS Mammals. 486 records from El código de barras de las especies NOM-059 de mamíferos del Noroeste de México. 66 records from Notes on the shrimp genus Palaemon Weber, 1795 (Crustacea, Decapoda, Palaemonidae) and related genera from Taiwan. 14052 records from Plant specimens of Horaiji-san Museum of Natural History. 23 records from Pachyrhynchus elenae Rukmane, 2016, a new synonym of Pachyrhynchus phaleratus Waterhouse, 1841 (Coleoptera: Curculionidae: Entiminae). 5 records from Scissurella nesbittae, new species, from the Gries Ranch Formation, Lewis County Washington State (Gastropoda: Vetigastropoda: Scissurellidae). 15 records from Body Mass, Bone " Strength Indicator, " and Cursorial Potential of Tyrannosaurus rex. 19 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 6 records from Taxonomic status of the barbastelles (Chiroptera: Vespertilionidae: Barbastella) from the Japanese archipelago and Kunashir Island. 4 records from Ompok argestes, a new species of silurid catfish endemic to Sri Lanka (Teleostei: Siluridae). 1 records from A new species of Homatula from the Red River drainage in Yunnan based on morphological and genetic data (Teleostei: Nemacheilidae). 43598 records from Mammals housed at MHNG, Geneva. 12 records from Two new ‘ Asura - like’ Cyana Walker, 1854 from Africa (Lepidoptera, Erebidae, Arctiinae). 2656 records from Swiss Psyllid (Hemiptera) Collections - Basel. 14 records from Four new species of Plumachaetas Salmon (Collembola: Entomobryoidea) from Oceania with comments on the genus and a key to species. 45 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 2 records from New species of Trichomycterus (Siluriformes: Trichomycteridae) lacking pelvic fins from Paranapanema basin, southeastern Brazil. 2 records from Spockia tagala gen. and sp. nov. a new monotypic genus of Asopinae (Hemiptera: Heteroptera: Pentatomidae) from the Philippines. 225 records from UWIZM Mantodea. 5 records from A new and five rare bdelloids from Korea. 536 records from Distribución actual y potencial de veinte especies de hongos silvestres comestibles en los bosques de coníferas del estado de Oaxaca. 7 records from Review of the Oriental leafhopper genus Parafagocyba Kuoh & Hu (Hemiptera: Cicadellidae: Typhlocybinae: Typhlocybini), with descriptions of three new species from China. 10 records from Validation of the status of a species with high CO 1 and low nuclear genetic divergences: the scab mite Caparinia ictonyctis stat. res. (Acariformes: Psoroptidae) parasitizing the African hedgehog Atelerix albiventris. 659 records from Taxonomía y prospección del hábitat de las poblaciones de Bursera sect. Bullockia con especial énfasis en las especies afines al 'linaloe', B. aloexylon (Schiede ex Schlecht.) Engl.. 187 records from Mollusca specimens of Kuroshio Biological Research Foundation. 23 records from Description of the female of the cellar spider Mesabolivar guapiara (Araneae, Pholcidae) from Mata Atlântica, Brazil. 1548 records from UNM Earth Sciences Collection (Arctos). 5 records from Neue Arten der Gattung Ypsiloncyphon KLAUSNITZER, 2009 (Coleoptera, Scirtidae) aus der Orientalischen Region II (215. Beitrag zur Kenntnis der Scirtidae). 55 records from New records of ant species from Yunnan, China. 1825 records from Caracterización biológica en la Serranía de San Lucas 2015. 250 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 1315 records from Bird specimens of Komatsu City Museum. 1 records from First occurrence of Anacroneuria singularis Righi-Cavallaro & Lecci, 2010 (Plecoptera: Perlidae) in Rondônia, western Amazonia, Brazil. 67 records from A survey of Phrurolithidae (Arachnida: Araneae) in southern Caucasus, Iran and Central Asia. 2 records from Description of larva of Euphaea superba Kimmins, 1936 (Odonata: Zygoptera: Euphaeidae) from China. 18 records from A new species of Paratelmatobius (Anura: Leptodactylidae: Paratelmatobiinae) from the Atlantic Forest of southern Brazil. 2 records from Cacoplistes (Laminogryllus) brevisparamerus sp. nov., a new species of Cachoplistinae (Orthoptera: Phalangopsidae) from Guangxi, China. 3 records from Description and life cycle of the hydrozoan Hydractinia uniformis, sp. nov. (Cnidaria: Hydrozoa: Hydractiniidae), from the coast of southeastern Brazil. 21 records from Three new species of the genus Neuquenaphis (Hemiptera, Aphididae, Spicaphidinae) from southernmost South America. 13 records from Three new species of moth flies (Diptera, Psychodidae, Psychodinae) from the Afrotropical Region. 12 records from On the spider genus Syspira Simon, 1895 (Araneae: Miturgidae) in the Caribbean: four new species from Dominican Republic. 14859 records from Invertebrate Bycatch Collection (Archive Pooling). 202 records from Collection Crustacea - ZSRO. 8 records from Sponge fauna of the New Siberian Shoal: biodiversity and some features of formation. 10 records from Two new species of Ankareus Kerremans (Coleoptera: Buprestidae: Haplostethinae) from southern Africa. 1 records from Key to species of the genus Pachymetopius Matsumura (Hemiptera: Cicadellidae: Stegelytrini) with description of a new species from China. 6 records from Cambarus (C.) appalachiensis, a new species of crayfish (Decapoda: Cambaridae) from the New River Basin of Virginia and West Virginia, USA. 152 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 11 records from Dysaphis (Dysaphis) kadyrovi sp. nov. — a new aphid species (Hemiptera: Aphididae) from Tajikistan. 12 records from A systematic appraisal of the types of ten species of Otostigmus (Parotostigmus) (Scolopendromorpha, Scolopendridae, Otostigminae). 3 records from Revision of the genus Allometopon Kertész (Diptera: Clusiidae). 3 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura Diogenidae) from shallow coastal waters in Japan. 21 records from Four new species of the genus Diaphorus (Diptera: Dolichopodidae) from China. 8 records from A taxonomic review of the genus Dicranorhina Shuckard (Hymenoptera: Crabronidae: Crabroninae) from the Indian subcontinent with the description of three new species from Southern Western Ghats. 8 records from American Asteraceae-feeding Astrotischeria species with a highly modified, three-lobed valva in the male genitalia (Lepidoptera, Tischeriidae). 46 records from A revision of Japanese Torymus Dalman (Hymenoptera: Torymidae). 5 records from Two new orthoclad species from Colombian Andes (Diptera: Chironomidae). 1 records from Ueber Chilopoden aus westbalkanischen Hoehlen. 16276 records from Coleoptera collection of Uunio Saalas. 423 records from Collembola of the Chernaya river basin. 8 records from Validation of the names of eight species of Blattaria according to the Rules of Zoological Nomenclature. 585 records from Checklist and taxonomic changes for Central and South American Philonthina (Coleoptera: Staphylinidae). 18039 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 38 records from A review of the genus Evonima Walker, 1865 from China with description of a new species (Lepidoptera, Nolidae, Nolinae). 28 records from Anfibios y reptiles de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO.
Keywords: GBIF; biodiversity; species occurrences